Website Company Profile Perumahan Cluster Pesona Mandiri, PT. Inras Jaya Mandiri. - Fadilillah Ramadhan; Heldi Heldi (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The purpose of this design is to produce alternative media for consumers of the Pesona Mandiri Cluster Housing to place property orders, check property availability, property prices and details from Pesona Mandiri Cluster housing. The initial problems encountered were the lack of property sales as a result of ineffective product marketing, promotions in online media that did not reach the market, and the absence of media such as websites that could make it easier for consumers to check properties online. Another problem encountered is the appearance of the property which is not packaged properly through online media. The 4D design method goes through stages, the Define Stage, the Design Stage, the Develop Stage, and the Dissemination Stage. The process uses 5w + 1h data analysis namely, what, who, where, when, why, and how. The results of the website design produce media, namely the Mobile Website as a medium that can solve the problems encountered, order property online, detail the property, check property availability, and check property online. In addition, the final supporting media works were designed: Name Cards, Manual Books, T-Shirt Shirts, X Banners, Posters, Social Media, Lanyards, and Snelhecter Folders.